IMPLICAÇÕES DO USO DE SMARTPHONES COMO FERRAMENTAS DE INTERATIVIDADE PARA PARTICIPAÇÃO NO CONTEXTO DA CELEBRAÇÃO DA SANTA MISSA - Neves, Pablo Diego de Araújo (2015)
This research aims at identifing and analyzing the implications of smartphones usage during the celebration of Holy Mass, in the context where such devices are used directly as interactivity tools among the faithfuls and the liturgy celebration, seeking to expand the multimediatic possibilities of these devices within the religious practice of its members. For this we used the application Católico Orante developed for this purpose, in order to provide the experience of use of such devices in this particular context. The literature review presents both the media interactivity context of the catholic faithfuls with the celebration of Mass, as well as the theoretical basis related to the Mobile Interaction Device quoted above, correlating still with the reality of the applications with Catholic religious themes. The methodology used was the method of Case Study, from the approach of User Experience (UX), with the group of young people Javé Nessi from the Igreja Menino Jesus de Praga, in Sao Luís do Maranhão, from which elaborated a study report, where the results obtained in the research were presented. It was found that the use of smartphones in this context still has been limited to usability issues and rejected by cultural barriers within the community, although the positive assessments of the user experience have been more frequent.